Essay Review. Scientocracy: Why a Science Court Is Needed: Scientocracy: The Tangled Web of Public Science and Public Policy edited by Patrick J. Michael - Bauer, Henry (Journal of Scientific Exploration, 2020)
The Introduction is spot on: “”Science can be a force for good, and it has enhanced our lives in countless ways, but even a cursory look at the 20th century shows that what passes for science can be detrimental” (p. 1).